Analisis Komparatif Kebijakan Perpajakan Atas Kegiatan Filantropi - Tri Maruli Sidabutar; Poltak Maruli John Liberty Hutagaol; Jasman Jasman (Journal of Applied Accounting and Taxation, 2020)
This study aims to analyze tax exemption and tax deduction policies on philanthropic activities in Indonesia and some other countries as a basis of recommendation in improving taxation policies to encourage philanthropic activities in Indonesia. Comparative analysis was conducted towards the similar policies in 4 selected namely, the United States, Myanmar, Sri Lanka, and Malaysia. The data used in this study were obtained from the CAF World Giving Index 10th report, A Global Philanthropy Legal Environment Index, the World Bank List of economies 2019, and tax regulations from the selected countries. Data analysis was conducted through comparative analysis methods supported by primary data, namely the results of interviews and secondary data, namely the results of literature reviews. The results of the analysis show that the tax exemption and tax deduction policies for philanthropic activities in Indonesia are adequate. There are several tax exemption and tax deduction policies on philanthropic activities from the selected countries that can be used as a basis of recommendation and consideration in the formulation and improvement of the related tax policies in Indonesia.